Metal magnetic memory field characterization at early fatigue damage based on modified Jiles-Atherton model - Xu, Ming-xiu; Xu, Min-qiang; Li, Jian-wei; Xing, Hai-yan (Journal of Central South University, 2012)
In order to propel the development of metal magnetic memory (MMM) technique in fatigue damage detection, the Jiles-Atherton model (J-A model) was modified to describe MMM mechanism in elastic stress stage. A series of rotating bending fatigue experiments were conducted to study the stress-magnetization relationship and verify the correctness of modified J-A model. In MMM detection, the magnetization of material irreversibly approaches to the local equilibrium state M 0 instead of global equilibrium state M an under cyclic stress, and the M 0 − σ curves are loops around the M an − σ curve. The modified J-A model is constructed by replacing M an in J-A model with M 0 , and it can describe the magnetomechanical effect well at low external magnetic field. In the rotating bending fatigue experiments, the MMM field distribution in normal direction around cylinder specimen is similar to the stress distribution, and the calculation result of model coincides with experiment result after some necessary modifications. The MMM field variation with time at a certain point in fatigue process is divided into three stages with the variation of stable stress-stain hysteresis loop, and the calculation results of model can explain not only the three stages of MMM field changes, but also the different change laws when the applied magnetic field and initial magnetic field are different. The MMM field distribution in normal direction along specimen axis reflects stress concentration effect at artificial defect, and the magnetic signal fluctuates around the defect at late fatigue stage. The calculation results coincide with the initial MMM principle and can explain signal fluctuates around the defect. The modified J-A model can explain experiment results well, and it is fit for MMM field characterization.